About Characters and the Dirichlet Kernel on Vilenkin Groups - Pepić, Medo (Sarajevo Journal of Mathematics, 2024)
In this paper we study properties of characters and the Dirichlet kernel on Vilenkin groups which are of key importance for analyzing convergence, integrability and summability of Fourier-Vilenkin series. 2000 Mathematics Subject Classification. 42C10, 43A40